Rate Equations and Kinetic Parameters of the Reactions Involved in Pyrite Oxidation by Thiobacillus ferrooxidans - Lizama, Hector M. (1989)
Rate equations and kinetic parameters were obtained for various reactions involved in the bacterial oxidation of pyrite. The rate constants were 3.5 μM Fe(2+) per min per FeS(2) percent pulp density for the spontaneous pyrite dissolution, 10 μM Fe(2+) per min per mM Fe(3+) for the indirect leaching with Fe(3+), 90 μM O(2) per min per mg of wet cells per ml for the Thiobacillus ferrooxidans oxidation of washed pyrite, and 250 μM O(2) per min per mg of wet cells per ml for the T. ferrooxidans oxidation of unwashed pyrite. The K(m) values for pyrite concentration were similar and were 1.9, 2.5, and 2.75% pulp density for indirect leaching, washed pyrite oxidation by T. ferrooxidans, and unwashed pyrite oxidation by T. ferrooxidans, respectively. The last reaction was competitively inhibited by increasing concentrations of cells, with a K(i) value of 0.13 mg of wet cells per ml. T. ferrooxidans cells also increased the rate of Fe(2+) production from Fe(3+) plus pyrite.